Peningkatkan Ketrampilan Membaca Siswa Kelas XB SMA Negeri 5 Kupang Melalui Penggunaan Media Wordwall - Pasos, Arnaldo D. S.; Margareta, Karus M.; Djerahi, Evarista Yulia (Jurnal Lazuardi, 2024)
Abstract The aim of this research is to improve students' ability to learn and read through the use of the educational game media Wordwall in the XB class of SMA Negeri 5 Kupang. Initial observations show that the monotonous and non-interactive Indonesian language learning method causes students to be less interested and active. Classroom Action Research (CAR) was used, which consists of four phases: planning, implementation, evaluation, and reflection. The research was conducted in three cycles, and each cycle involved various efforts to improve the learning process. The research results showed that students improved their reading skills and their learning engagement after using Wordwall media. The results of observations and interviews show that students are more interested and involved in learning, and the formative assessment scores increase. Therefore, students at SMA Negeri 5 Kupang improve their reading and learning skills by using Wordwall media. Keywords: reading skills, Wordwall, educational game media, Classroom Action Research, SMA Negeri 5 Kupang